(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2023)
The female figure in cinematographic art has been shown through archetypes and performing different functions. We propose in this study to analyze female characters through the audiovisual narrative in two emblematic films of Hitchcock’s cinematography: Spellbound and Vertigo, in which women are seen as empowered, but also subjected to a denial of their own identity. We consider that the treatment of women in the cinema of that time lies in the social situation of the same, suffering a discriminatory treatment, which is admitted by the female characters justifying it in a crush, which annuls the own personality.